Glycation of Wild‐Type Apomyoglobin Induces Formation of Highly Cytotoxic Oligomeric Species. Issue 11 (November 2015) - Iannuzzi, Clara; Carafa, Vincenzo; Altucci, Lucia; Irace, Gaetano; Borriello, Margherita; Vinciguerra, Roberto; Sirangelo, Ivana
<x xml:space="preserve">Abstract</x> Protein glycation is a non‐enzymatic, irreversible modification of protein amino groups by reactive carbonyl species leading to the formation of advanced glycation end products (AGEs). Several proteins implicated in neurodegenerative diseases have been found to be glycated in vivo and the extent of glycation is related to the pathologies of the patients. Although it is now accepted that there is a direct correlation between AGEs formation and the development of neurodegenerative diseases related to protein misfolding and amyloid aggregation, several questions still remain unanswered: whether glycation is the triggering event or just an additional factor acting on the aggregation pathway. We have recently shown that glycation of the amyloidogenic W7FW14F apomyoglobin mutant significantly accelerates the amyloid fibrils formation providing evidence that glycation actively participates to the process. In the present study, to test if glycation can be considered also a triggering factor in amyloidosis, we evaluated the ability of different glycation agents to induce amyloid aggregation in the soluble wild‐type apomyoglobin. Our results show that glycation covalently modifies apomyoglobin and induces conformational changes that lead to the formation of oligomeric species that are not implicated in amyloid aggregation. Thus, AGEs formation does not trigger amyloid aggregation in the wild‐type apomyoglobin but only induce the formation of soluble oligomeric species able to affect cell viability. The molecular bases of cell toxicity induced by AGEs formed upon glycation of wild‐type apomyoglobin have been also investigated. J. Cell. Physiol. 9999: 2807–2820, 2015. © 2015 Wiley Periodicals, Inc.